2017
DOI: 10.1002/etc.3876
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and human dietary assessment of fluoroquinolones antibiotics in cultured fish around Tai Lake, China

Abstract: Fluoroquinolone antibiotics are widely used in the production of aquatic products and considered to be a significant contributing factor to the burden of both natural and aquaculture environments. However, the main types of fluoroquinolones present in aquaculture systems have not been determined. The objectives of the present study were to explore the occurrence of residual fluoroquinolone antibiotics in fish muscle tissues sampled from across the entire aquaculture season in the Tai Lake basin in China and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Neural stem cells are multipotent stem cells that have been suggested as a therapeutic agent to enhance the recovery of injured tissues in neuroinflammatory diseases [44]. Park and colleagues tested the effects of GV1001, a novel antioxidant agent, derived from human telomerase reverse transcriptase, on in vitro-cultured mouse NSCs.…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…Neural stem cells are multipotent stem cells that have been suggested as a therapeutic agent to enhance the recovery of injured tissues in neuroinflammatory diseases [44]. Park and colleagues tested the effects of GV1001, a novel antioxidant agent, derived from human telomerase reverse transcriptase, on in vitro-cultured mouse NSCs.…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…(a) Residues of QNs and SAs in muscle and liver of marine aquaculture products of Guangdong Province, South China. , Lipid content of muscle and liver (because each individual has a different lipid content, here are just Takifugu flavidus and Pampus cinereus as examples). , (b) Comparison of ∑QNs (enrofloxacin, norfloxacin, and ciprofloxacin) and SAs (sulfadiazine, sulfamethoxazole, sulfamethazine, and sulfadimidine). ,,,,,,,,,, (c) Mean concentration of oxytetracycline (top antibiotic in aquaculture) from China, South Korea, U.S.A., Argentina, and Brazil. , …”
Section: Residues Of Antibiotics In Cultured Aquatic Productsmentioning
confidence: 99%
“…Previous studies reported that half the amount of antibiotics produced in China, the world’s largest producer and user of antibiotics, ended up in animal feed in recent years, meaning that approximately 105 000 tonnes was used for animal consumption . Antibiotics via oral administration, bath, pond sprinkle, and injection can prevent and treat aquaculture diseases, and some of them are even used as growth promoters. However, antibiotics also cause stresses on the aquatic environment . Numerous studies have investigated the residues of antibiotics in water bodies and sediments and confirmed the antibiotic contamination. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations